Parking lot landscape development an environmental design instructional module. - Center for Environmental Design Education and Research (U.S.) (Reston, Va. : Environmental Design Press, 1978)
Illustrates how landscape development can be used to relieve the harshness and unpleasantness of large parking areas.
Keywords: Parking lots -- Landscape architecture